METHOD DEVELOPMENT AND VALIDATION OF RICINOLEIC ACID BY HPTLC - Raghu Duraisamy; Parthasarathy Mahadevan; Baskaran Siva; Ramesh Jaya Rama Chandra Reddy; Gadevaru Sarathchandra (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Ricinoleic acid, a toxic compound found in castor seeds (Ricinus communis L.), can be lethal when inhaled, ingested, or injected at doses of 5-10 pg/kgto human or animals. This study presents a validated, rapid, and precise high-performance thin-layer chromatographic (HPTLC) methodfor its quantification. Separation was achieved on silica gel 60 F254plates using a mobile phase oftoluene, ethyl acetate and acetate acid (6:4:0.2 v/v/v). Densitometric scanning at 450 nm detected ricinoleic acid with an Rfvalue of 0.66 (±0.04). Linearity was observed in the range of 20-100 ng/spot with R = 0.998 ± 2.62%.